معايير مقياس الطفل التوحدي بالقوة التمييزية لفقراته لدى عينة من مدينة مصراتة تتراوح أعمارهم من (3 _ 10) سنوات (Faculty of Education Scientific Journal, 2024)
This study focuses on autism and its crucial aspects, including its definition, major symptoms, diagnostic criteria, and distinguishing features from intellectual disability. It reviews current research on diagnostic measures for autism. The primary objective of this research is to examine the discriminative power of the paragraphs in the Autism Child Scale and establish criteria for its effective implementation. The findings indicate that all paragraphs, except for paragraphs 9, 10, 11, and 26, possess valid discriminative power for diagnosing autism. Consequently, these paragraphs were excluded, resulting in a refined scale consisting of 26 items.Furthermore, the study analyzed the differences in scores between males and females with autism, employing a t-test on a sample of 26 children, evenly distributed across genders. The results revealed that the observed difference (1.17) was not statistically significant. Similarly, when comparing two age groups (3-6 and 7-10 years), no statistically significant differences were found. The t-value was 1.56 for both groups, with a sample size of 15 in each group.Additionally, the study examined the disparities between the highest 27% and lowest 27% of total scores on the Autism Child Scale. The analysis demonstrated statistically significant differences, favoring the higher-scoring group, with a t-value of 22.6 for a sample size of 35 in each group.Consequently, the researcher established criteria by converting raw scores into percentile ranks, and then transforming them into standard scores, ultimately resulting in an average autism score of 100 with a standard deviation of 10. These criteria can be utilized to determine autism diagnosis and assess the severity of autism in children.Based on the findings, the researcher recommends the establishment of specialized centers to cater to children with varying degrees of autism severity. Additionally, periodic assessments every three to six months are suggested to monitor the progress of individual cases. It is further recommended to standardize the use of the Gilliam Autism Rating Scale for diagnosing autism within the local context of Misrata City and develop a standardized autism scale suitable for the specific environment in Libya, incorporating the latest research on autism, diagnosis, and major symptoms.